Psychological characteristics and their development in Olympic champions - Gould, D.; Dieffenbach, K.; Moffett, A. (Journal of Applied Sport Psychology, 2002)
This study was designed to examine psychological characteristics and their development in Olympic champions. Ten U.S. Olympic champions (winners of 32 Olympic medals) were interviewed, as were one of their coaches ( n = 10), and a parent, guardian, or significant other ( n = 10). A battery of psychological inventories was also administered to the athletes. It was found that the athletes were characterized by: (a) the ability to cope with and control anxiety; (b) confidence; (c) mental toughness/resiliency; (d) sport intelligence; (e) the ability to focus and block out distractions; (f) competitiveness; (g) a hard-work ethic; (h) the ability to set and achieve goals; (i) coachability; (j) high levels of dispositional hope; (k) optimism; and (l) adaptive perfectionism. Results also revealed that a number of individuals and institutions influenced the athletes' psychological development including the community, family, the individual himself or herself, non-sport personnel, sport environment personnel, and the sport process. Coach and family influences were particularly important. Ways in which these sources influenced the athletes were both direct, like teaching or emphasizing certain psychological lessons, and indirect, involving modeling or unintentionally creating certain psychological environments. Psychological characteristic findings verified current sport psychological research on psychological characteristics associated with peak performance (Williams & Krane, 2001). They also suggest that adaptive perfectionism, dispositional hope, and high levels of optimism are new variables to consider. Results are also discussed relative to Bloom's (1985), Côtè's (1999) and Csikzentmihalyi, Rathunde, Whalen, and Wong's (1993) talent development research. Practical implications focus on implementing parenting and coaching practices related to the development of psychological characteristics associated with athletic success.